Penerapan Evidence Based Practice Chin Tuck Againts Resistance (CTAR) dalam Penanganan Disfagia pada Pasien Stroke - Rinawati, Rinawati; Jumaiyah, Wati; Yunitri, Ninik; Agung, Rizki Nugraha; Nurhayati, Elis (MAHESA : Malahayati Health Student Journal, 2024)
ABSTRACT The Chin Tuck Against Resistance (CTAR) intervention is rarely utilized by nurses in treating dysphagia among stroke patients. Symptoms arising from a stroke can differ based on the affected brain area, encompassing speech disorders, chewing and swallowing difficulties (dysphagia), limb paralysis or weakness, personality alterations, emotional disturbances, diminished cognitive abilities, impaired urinary function, and others. The use of Evidence-Based Nursing Practice (EBNP) is conducted to comprehend the impact of implementing chin tuck against resistance (CTAR) on improving swallowing muscle strength in stroke patients with dysphagia. In this study, the data were analyzed using univariate data analysis to evaluate the demographic characteristics and swallowing ability profiles of each respondent. Furthermore, the statistical test of influence was conducted using a paired t-test to assess changes in swallowing ability after undergoing CTAR rehabilitation exercises. Sampling in this study utilized the total sample method, involving 8 respondents. The CTAR intervention has been shown to significantly improve swallowing ability in stroke patients. The results indicate a meaningful increase from an average of 84.3 to 91.7 post-intervention, with an effect size of 4.59 and a p-value of 0.022, demonstrating the statistical effectiveness of this therapy. Furthermore, CTAR exercises are convenient to implement, time-efficient, and can be performed by patients without disrupting their daily routines. To enhance its effectiveness, it is recommended to involve patients and their families in the education process, enabling them to continue the exercises independently. The simplicity of these exercises facilitates nurses in providing interventions during nursing care for stroke patients experiencing dysphagia. Keywords: Evidence Based Practice Chin Tuck Against Resistance (CTAR), Dysphagia, Stroke Patients  ABSTRAK Intervensi Chin Tuck Exercise (CTAR) jarang digunakan oleh perawat untuk mengatasi disfagia pada pasien stroke. Gejala yang muncul akibat stroke dapat bervariasi tergantung pada area otak yang terkena, termasuk gangguan berbicara, kesulitan mengunyah dan menelan (disfagia), kelumpuhan atau kelemahan anggota gerak, perubahan kepribadian, gangguan emosi, penurunan fungsi kognitif, gangguan fungsi berkemih, dan lainnya. Penggunaan Praktik Keperawatan Berbasis Bukti (EBNP) dilakukan untuk memahami dampak dari penerapan chin tuck against resistance (CTAR) terhadap peningkatan kekuatan otot menelan pada pasien stroke dengan disfagia. Pada penelitian ini, data dianalisis menggunakan analisis data univariat untuk mengevaluasi karakteristik demografi dan gambaran kemampuan menelan pada setiap responden. Selanjutnya, uji statistik pengaruh dilakukan dengan uji paired t-test untuk menilai perubahan kemampuan menelan setelah menjalani latihan rehabilitasi CTAR. Pengambilan sampel dalam penelitian ini menggunakan metode total sampel dengan melibatkan 8 responden. Intervensi CTAR terbukti secara signifikan meningkatkan kemampuan menelan pada pasien stroke. Hasil menunjukkan peningkatan yang berarti dari rata-rata 84.3 menjadi 91.7 setelah intervensi, dengan besaran efek sebesar 4.59 dan nilai p-value sebesar 0.022, menunjukkan keefektifan terapi ini secara statistik. Lebih lanjut, latihan CTAR memberikan kemudahan dalam pelaksanaan, tidak memakan waktu lama, dan dapat dilakukan oleh pasien tanpa mengganggu rutinitas harian. Untuk meningkatkan efektivitasnya, disarankan untuk melibatkan pasien dan keluarganya dalam proses edukasi, sehingga mereka dapat melanjutkan latihan secara mandiri. Kesederhanaan latihan ini memudahkan perawat dalam memberikan intervensi selama asuhan keperawatan pada pasien stroke yang mengalami disfagia. Kata Kunci: Praktek Berbasis Bukti Chin Tuck Melawan Resistensi (CTAR), Disfagia, Pasien Stroke